2000
DOI: 10.2337/diabetes.49.8.1390
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphism T(-107)C of the paraoxonase PON1 gene is a risk factor for coronary heart disease in type 2 diabetic patients.

Abstract: The serum enzyme paraoxonase (PON) protects LDLs from oxidative stress. We recently identified promoter polymorphisms of the PON gene that strongly affect gene expression and serum levels of the enzyme. The present study tested the hypothesis that promoter polymorphism T(-107)C could be a risk factor for vascular disease in type 2 diabetic patients by virtue of its ability to modulate serum concentrations of the antioxidant enzyme. The low-expressor genotype (TT) was associated with significantly lower serum P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
2
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 20 publications
10
69
2
4
Order By: Relevance
“…This has been confirmed independently (8 -11), although not consistently (12,13). In subsequent studies we have shown that PON1 promoter polymorphisms, which affect promoter activity and serum PON1 concentrations (14), are also independent risk factors for coronary disease (15). This is consistent with gene expression being a determinant of the influence of PON1 on vascular disease.…”
Section: Paraoxonase-1 (Pon1)supporting
confidence: 70%
“…This has been confirmed independently (8 -11), although not consistently (12,13). In subsequent studies we have shown that PON1 promoter polymorphisms, which affect promoter activity and serum PON1 concentrations (14), are also independent risk factors for coronary disease (15). This is consistent with gene expression being a determinant of the influence of PON1 on vascular disease.…”
Section: Paraoxonase-1 (Pon1)supporting
confidence: 70%
“…Another possibility is that relatively reduced enzyme activity rather than increased absolute PON1 activity promotes vascular complications. Some have reported that a higher LDL cholesterol-to-PON concentration ratio may indicate a reduced capacity of the enzyme to limit LDL oxidation (22). The low-activity allele at the PON1 gene has also been associated with a less harmful lipoprotein profile (23).…”
Section: Discussionmentioning
confidence: 99%
“…There may be linkage [32,34] or at least a complex interaction [36] between the 192 site and the 107 promoter polymorphism, which could confound the association between the R192 allele and paraoxonase activity in earlier studies.…”
Section: Activity Hdl and Apoa-1 According To Pon55 Genotypementioning
confidence: 97%